Topography changes of rhodium electrodes induced by the application of fast periodic potential routines - Méndez, Eduardo (2003)
The surface structure of polycrystalline rhodium electrodes in contact with aqueous sulfuric acid was modified by chemical etching with hot concentrated acid or by applying fast square waves with an upper potential equal to 1.55 V and a lower potential within the –0.75 V to –0.35 V range. Polycrystalline rhodium and chemical etched electrodes were characterized by voltammetry, Cu underpotential deposition (upd) and X-ray diffraction. For electrofaceted surfaces were used voltammetry, Cu upd and SEM, revealing that two modified rhodium electrodes exhibit similar voltammetric characteristics as those found for Rh(111) and Rh(110) single crystals, and a third surface with an equal distribution of (110) and (111) planes. In addition, the upd of Cu on those surfaces corroborated the existence of those crystallographic planes. SEM micrographs show surface structures with a high density of terraces and steps. A mechanism of faceting is proposed.